The Needs of Internal Supervision in Educational Institutions to Enhance Students’ English Proficiency According to the CEFR Framework under the Chiang Rai Province Vocational Education Office - Onkhamleaung, Panalee; Meeprom, Kasidit (Vocational Education Central Region Journal, 2026)
The purposes of this research were to study The Needs of Internal Supervision in Educational Institutions to Enhance Students’ English Proficiency According to the CEFR Framework under the Chiang Rai Province Vocational Education Office. The population used in the research was 49: administrators and teachers, from government vocational education institutions. The statistics used for data analysis were percentage, mean (μ), standard deviation (σ), and needs analysis using the Priority Needs Index formula. It was found that the current overall condition was at a moderate level and the overall desired condition was at a high level. The needs of internal supervision according to the CEFR framework had an overall needs index value (PNImodified=0.285). The aspect with the highest needs was the assessment of supervision results (PNImodified=0.296), followed by the supervision implementation (PNImodified=0.294), the encouragement of supervisors (PNImodified=0.286), the pre-supervision knowledge (PNImodified=0.282) and supervision planning aspect (PNImodified=0.266).